Cloning and expression of the human fibroblast growth factor 10 (hfgf-10) in E. coli - Nhi, Nguyen Bich; Suzuki, Masashi (Academia Journal of Biology, 2015)
Full length hFGF-10 cDNA (624 bp - 208 amino acids) was amplified from the human brain total RNA by reverse transcription-polymerase chain reaction (RT-PCR) and cloned into the pCR Script cloning vector for the verification of the DNA sequence as hFGF-10 (accession number AB 002097 in DDBJ and GenBank Nucleotide Sequence Databases). For the expression of hFGF-10 in E.coli, the cDNA encoding hFGF-10 (amino acids 40-208 eliminating the N-terminal sequence) was amplified and cloned into the pET-3C expression vector with cloning sites NdeI/BamHI and transfected into the BL21(DE3)pLysS cells. E.coli cells bearing the recombinant plasmid were grown in LB medium containing ampicillin and chloramphenicol until OD 600 nm reached 0.3 and the expression of the hFGF-10 was induced by adding IPTG and followed by incubation at 37°C or 30°C for 3h. Cells were centrifuged, resuspended in GET buffer and lysed by sonication. The supernatants were cleared by the centrifugation and analysed by SDS-PAGE. The results showed that the hFGF-10 recombinant protein was produced and its size was about 20kDa.